Impact of Coxiella burnetii-associated abortions in Finnish forest reindeer within a zoo on public health appeared negligible succeeding mitigation strategies - Marleen M. Kannekens-Jager; Andries A. Kampfraath; Christine Kaandorp; Annemieke Dinkla; Frank Harders; Lars Ravesloot; Pieter Jacobs; Judith M. A. van den Brand; Erik A. W. S. Weerts; Senta L. D. Janssen; Lenny M. J. Engelen; Amanja Verhaegh-Haasnoot; et al. (Frontiers in Veterinary Science, 2026)
Coxiella burnetii is a Gram-negative, ubiquitous bacterium that may infect many animal species as well as humans. In this study, transmission of C. burnetii during an outbreak of abortions in a herd of Finnish forest reindeer ( Rangifer tarandus fennicus ) in a Dutch zoo was investigated. Diagnostic sampling showed positive C. burnetii antigen detection with qPCR from vaginal swabs and positive C. burnetii serology (ELISA) in all cases of abortion (4/4) and in one animal after normal parturition. Placental tissue ( n = 2) and fetal liver tissue ( n = 1) retrieved after two abortions were positive for C. burnetii infection by qPCR and immunohistochemistry. Histological staining revealed the presence of C. burnetii in the placenta, indicating infection. Follow-up diagnostic approaches were aimed toward isolation, strain typing, and molecular analysis. Direct sequencing from placental tissue resulted in a full genome and plasmid sequence. Whole-genome sequence analysis, including multilocus variable-number tandem repeat analysis (MLVA), resulted in similarities with a C. burnetii strain previously found in cattle. A One Health approach was implemented, guiding efforts to prevent and monitor human Q fever following potential exposure to C. burnetii . No human Q fever cases were reported, and additional serological testing of exposed zoo personnel showed no indications of infection. This article describes the first documented case of clinical abortions caused by C. burnetii in Finnish forest reindeer, offering new insights into coxiellosis in non-domestic animals and highlighting lessons to inform future preparedness and response.